Sentinel Lymph Node Biopsy in Pure DCIS: Is It Necessary?. (14th May 2012) - Boler, D. E.; Cabioglu, N.; Ince, U.; Esen, G.; Uras, C.
Abstract : Introduction. Sentinel lymph node biopsy (SLNB) in patients with pure ductal carcinoma in situ (DCIS) has been a matter of debate due to very low rate of axillary metastases. We therefore aimed to identify factors in a single institutional series to select patients who may benefit from SLNB. Material and Methods. Patients, diagnosed with pure DCIS (n = 63 ) between July 2000 and March 2011, were reviewed. All the sentinel lymph nodes were examined by serial sectioning (50 μm) of the entire lymph node and H&E staining, and by cytokeratin immunostaining in suspicious cases. Results. Median age was 51 (range, 30–79). Of 63 patients, 40 cases (63.5%) with pure DCIS underwent SLN, and 2 of them had a positive SLN (5%). In both 2 cases with SLN metastases, only one sentinel lymph node was involved with tumor cells. Patients who underwent SLNB were more likely to have a tumor size >30 mm or DCIS with intermediate and high nuclear grade or a mastectomy in univariate and multivariate analyses. Conclusion. In our series, we found a slightly higher rate of SLNB positivity in patients with pure DCIS than the large series reported elsewhere. This may either be due to the meticulous examination of SLNs by serial sectioning technique or due to our patient selection criteria or both.